COVID-19 amongst the Pandemic of Medical Student Mental Health - Komer, Leah (International Journal of Medical Students, 2020)
The medical community has been greatly impacted by the COVID-19 pandemic. As medical students, we face unique challenges and uncertainty during this time. While the world gears up to fight the battle with this physical illness, our battle with mental health should not be forgotten. Medical students are disproportionately affected by mental health issues and psychological distress. This experience piece aims to shed light on these challenges and provoke a discussion around mental health in medical students during these trying times.